PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN PELANGGAN YANG DIMEDIASI OLEH NILAI PELANGGAN PADA PRODUK MEREK DIAN PELANGI DI BANDA ACEH - Cut Mardaliana, Fakhrurrazi Amir (Departemen Manajemen, 2018)
Abstract: This study aims to examine the effect of Product Quality and Price of Cuatomer Satisfaction mediated by Customer Value on Dian Pelangi brand product users in Banda Aceh. Retrieval method the sample in this study used purposive sampling with samples totaling 125 respondents. The results showed that product quality and prices have a positive and significant effect on customer value. Furthermore, product quality price and customer value have a significant effect towards customer satisfaction. Customer value is proven to mediate partially on the effect of product quality and price on customer satisfaction.Keywords: Product Quality, Price, Perceived Value, Customer Satisfaction